Quantum non-demolition readout of an electron spin in silicon - J. Yoneda (Nature Portfolio, 2020)
Conventional qubit readout methods in silicon spin qubits destroy the quantum state, precluding any further computations based on the outcome. Here, the authors demonstrate quantum non-demolition readout using a second qubit of the same kind, making for a scalable approach.